Learning Strategy towards Students’ Descriptive Writing Achievement Taught by Using Pick – List – Evaluate – Active – Supply – End Strategy - LENNY MARZULINA (Edukasi, 2018)
This study is an experimental study with a factorial design. The aims of the study were to find (1) the significant improvement on students’ descriptive writing achievement taught using PLEASE strategy, (2) the significant improvement in poor category taught by teacher’s strategy, (3) the significant difference on students' descriptive writing achievement taught by PLEASE and teacher’s strategy, (4) the significant difference in very good and fair categories taught by PLEASE strategy, (5) the influence of language learning strategy towards students' descriptive writing achievement in very good and fair categories, (6) the influence of language learning strategy towards students' descriptive writing achievement taught by PLEASE strategy, and (7) the interaction effects between language learning strategy toward students’ descriptive writing achievement taught by PLEASE and teacher’s strategies. In conducting my research activities, 72 out of 150 students were selected as the sample of the study using a two-stage cluster random sampling technique. The results of the study showed that first, the result analysis of measuring showed that significant improvement on students’ descriptive writing taught using PLEASE strategy using paired-sample test was found since the p-output (0.000) is lower than the significant level at 0.05. Second result analysis by using paired-sample test in measuring the significant improvement on students' descriptive writing achievement in poor category which was taught by using teacher strategy was found since the p-output (0.000) was less than the significance level at 0.05. Third analysis in measuring a significant difference on students' descriptive writing achievement which was taught by PLEASE and teacher’s strategy using independent-sample test was not found since the p-output (0.013) was greater than the significance level at 0,05. Fourth analysis in measuring the significant difference on students' descriptive writing achievement in very good and fair categories taught by PLEASE strategy using independent-sample test was not found since the p-output (0.286) was higher than the significance level at 0.05. Fifth result analysis on the influence of language learning strategy towards students' descriptive writing achievement in very good and fair categories using one-way ANOVA was found since the p-output (0.000) smaller than the significance level at 0,05. Sixth, the result analysis of measuring the influence of language learning strategy towards students' descriptive writing achievement taught by PLEASE strategy using one-way ANOVA was not found since the p-output (0.115) higher than the level of significance level at 0.05. The last analysis of measuring the interaction effects between language learning strategy toward students’ descriptive writing achievement taught by PLEASE and teacher strategy using two-ways ANOVA was not found since the p-output (0,430) was bigger than the significance level at 0,05